Animated Mathematics Learning Media on guru.tesonlineku.com using Plotagon Story and Lectora Inspire - Sagala, Prihatin Ningsih; Septiana, Dian; Widyastuti, Eri (Jurnal Ilmu Pendidikan, 2024)
This research aims to develop animated story-learning media that helps students improve their understanding of mathematical concepts. This research uses the ADDIE development (R and D) method, which consists of analysis, design, development, implementation, and evaluation stages. The sample research subjects consisted of 6 experts, two material, media, and language validator experts each, one teacher, 5 and 147 class VII students who assessed the practicality and effectiveness of the product being developed. Data was collected through expert validation, interviews with teachers, teacher and student response tests, and tests on students. At the same time, the N-Gain test was used to evaluate media effectiveness. Expert validation results show that the criteria are very valid, with an average score of 89 percent. The teacher and student response test showed an average score of 86 percent, which shows that the animated story media is practically used for mathematics learning. The N-Gain test of 67 percent shows that students' ability to understand mathematical concepts is increasing. Therefore, using animated stories to develop skills in understanding mathematical concepts is feasible, practical, and effective